Combined activity of Maruca vitrata multinucleopolyhedrovirus, MaviMNPV, and oil from neem, Azadirachta indica Juss and Jatropha curcas L., for the control of cowpea pests - Sokame, B.M.; Tounou, A.K.; Datinon, B.; Dannou, E.A.; Agboton, C.; Srinivasan, R.; Pittendrigh, Barry Robert; Tamò, Manuele (Elsevier, 2015)
The insecticidal activity of Maruca vitrata (F.) multi-nucleopolyhedrovirus ( Mavi MNPV) combined with oil from neem, Azadirachta indica Juss and Jatropha curcas L. (Euphorbiaceae) was studied under labo- ratory and fi eld conditions against three key insect pests of cowpea, Vigna unguiculata (L.) Walp. Second- instar Aphis craccivora Koch and Megalurothirps sjostedti Trybom nymphs, and third-instar M. vitrata larvae, all from laboratory colonies, were treated with various concentrations of one of the control agents separately or combined. Daily mortality was recorded for fi ve days ( A. craccivora and M. sjostedti nymphs) or fourteen days ( M. vitrata ) and the larval and pupal development as well as adult emergence were assessed. Combination of Mavi MNPV resulted in a signi fi cantly higher larval mortality in M. vitrata than treatment with either virus or botanical insecticide alone at the corresponding concentrations. Larvae of M. vitrata infected with Mavi MNPV and treated with botanical oils died sooner than those infected with only one control agent. Combinations of Mavi MNPV and botanical oils produced additive or synergistic effects. No evidence of antagonistic effects was noted. In fi eld experiments, the application of botanical insecticide and Mavi MNPV either alone or in combination was effective in reducing insect abundance over the four weeks, and preventing yield loss. In the fi rst fi eld season, where the M. vitrata population was higher, the combination of the virus and either of the botanical pesticides induced signi fi cantly higher yields than spraying chemical insecticide. Application of Mavi MNPV in combination with J. curcas and A. indica oil has proven to induce consistent Mavi MNPV infection in M. vitrata populations. The combined application of Mavi MNPV and botanical oils is discussed in the context of integrated pest management.The insecticidal activity of Maruca vitrata (F.) multi-nucleopolyhedrovirus ( Mavi MNPV) combined with oil from neem, Azadirachta indica Juss and Jatropha curcas L. (Euphorbiaceae) was studied under labo- ratory and fi eld conditions against three key insect pests of cowpea, Vigna unguiculata (L.) Walp. Second- instar Aphis craccivora Koch and Megalurothirps sjostedti Trybom nymphs, and third-instar M. vitrata larvae, all from laboratory colonies, were treated with various concentrations of one of the control agents separately or combined. Daily mortality was recorded for fi ve days ( A. craccivora and M. sjostedti nymphs) or fourteen days ( M. vitrata ) and the larval and pupal development as well as adult emergence were assessed. Combination of Mavi MNPV resulted in a signi fi cantly higher larval mortality in M. vitrata than treatment with either virus or botanical insecticide alone at the corresponding concentrations. Larvae of M. vitrata infected with Mavi MNPV and treated with botanical oils died sooner than those infected with only one control agent. Combinations of Mavi MNPV and botanical oils produced additive or synergistic effects. No evidence of antagonistic effects was noted. In fi eld experiments, the application of botanical insecticide and Mavi MNPV either alone or in combination was effective in reducing insect abundance over the four weeks, and preventing yield loss. In the fi rst fi eld season, where the M. vitrata population was higher, the combination of the virus and either of the botanical pesticides induced signi fi cantly higher yields than spraying chemical insecticide. Application of Mavi MNPV in combination with J. curcas and A. indica oil has proven to induce consistent Mavi MNPV infection in M. vitrata populations. The combined application of Mavi MNPV and botanical oils is discussed in the context of integrated pest management.The insecticidal activity of Maruca vitrata (F.) multi-nucleopolyhedrovirus ( Mavi MNPV) combined with oil from neem, Azadirachta indica Juss and Jatropha curcas L. (Euphorbiaceae) was studied under labo- ratory and fi eld conditions against three key insect pests of cowpea, Vigna unguiculata (L.) Walp. Second- instar Aphis craccivora Koch and Megalurothirps sjostedti Trybom nymphs, and third-instar M. vitrata larvae, all from laboratory colonies, were treated with various concentrations of one of the control agents separately or combined. Daily mortality was recorded for fi ve days ( A. craccivora and M. sjostedti nymphs) or fourteen days ( M. vitrata ) and the larval and pupal development as well as adult emergence were assessed. Combination of Mavi MNPV resulted in a signi fi cantly higher larval mortality in M. vitrata than treatment with either virus or botanical insecticide alone at the corresponding concentrations. Larvae of M. vitrata infected with Mavi MNPV and treated with botanical oils died sooner than those infected with only one control agent. Combinations of Mavi MNPV and botanical oils produced additive or synergistic effects. No evidence of antagonistic effects was noted. In fi eld experiments, the application of botanical insecticide and Mavi MNPV either alone or in combination was effective in reducing insect abundance over the four weeks, and preventing yield loss. In the fi rst fi eld season, where the M. vitrata population was higher, the combination of the virus and either of the botanical pesticides induced signi fi cantly higher yields than spraying chemical insecticide. Application of Mavi MNPV in combination with J. curcas and A. indica oil has proven to induce consistent Mavi MNPV infection in M. vitrata populations. The combined application of Mavi MNPV and botanical oils is discussed in the context of integrated pest management.